Analysis of the Effects of Rivalry and Dynamism on the Firm’s Competitive Position - Alexandre Teixeira Dias; Eva Jaqueline Rolim Gonçalves de Sousa; Jersone Tasso Moreira Silva; Wendel Alex Castro Silva (BBR: Brazilian Business Review)
The main objective of this study is to analyze the influences of dynamism and rivalry on the competitive position of US firms in the periods pre- and post-economic crisis of 2008, considering the role of firm size as a moderator. For this, data from firms operating in the manufacturing industry from 2001 to 2015 were used as a sample, analyzing the data through structural equation modeling. The model proposed in this study relates the constructs competitive position, dynamism and rivalry, using as a moderator the size of the firm. We found that the 2008 crisis influenced the environment in which the firms in the sample were inserted, causing a reduction in dynamism and rivalry. It was found that rivalry and firm size influenced competitive position, while dynamism, on the other hand, had little influence on competitive position. We also concluded that the dynamism of the industry has a direct influence on rivalry between firms.